Respuesta :

Answer:

6.357

Step-by-step explanation:

This is probably wrong

Step 1: Rewrite the equation

7(x+4)-6(x+3)=x+5

Step 2: Distribute

7(x+4)- 6(x+3) = x+5

7x+28-6x-18 = x+5

Step 3: Combine like terms

7x+ 28 -6x-18 = x+5

x+10=x+5

Step 4: To seclude x, subtract 5 on both sides (we choose 5 instead of 10, to avoid working with negatives)

x+10=x+5
-5 -5
________
x+5=x

Step 4: Subtract x on both sides

x+5=x
-x -x

5=0x

Step 5: Your answer (if I did this correctly) is 0

Hope this is right and it helps :)